Rational Design of A Novel Small-Molecule HIV-1 Inactivator Targeting Both gp120 and gp41 of HIV-1 - Pu, Jing; Dai, Yu; Wang, Qian; Lu, Lu; Zhang, Junqi; Xu, Wei; Xie, Lan; Wang, Shengqi; Yu, Fei; He, Xiaoyang; Jiang, Shibo (Frontiers in Pharmacology, 2021)
Virus inactivator can inactivate cell-free virions without relying on their replication cycle, potentially reducing the impact of viral infection on cells. Previously, we successfully constructed a HIV-1 protein inactivator, 2DLT, by conjugating the D1D2 region of CD4 to the fusion inhibitor T1144 via a 35-amino acid linker. Therefore, it targets both the CD4 binding site in gp120 and NHR region in gp41. Considering that small-molecule agents have the advantages of fast production, low cost, good stability, and oral availability, we herein report the design of a new small-molecule HIV-1 inactivator, FD028, by conjugating FD016 (an analog of NBD-556, a gp120-CD4 binding inhibitor) with FD017 (an analog of 11d, an HIV-1 fusion inhibitor). The results showed that FD028 inactivated cell-free virions at a moderate nanomolar concentration by targeting both HIV-1 gp120 and gp41. Moreover, FD028 has broad-spectrum inhibition and inactivation activity against HIV-1 resistant strains and primary isolates of different subtypes without significant cytotoxicity. Therefore, FD028 has potential for further development as an HIV-1 inactivator-based therapeutic.